Paying Attention: Overnight Returns and the Hidden Cost of Buying at the Open - Berkman, Henk; Koch, Paul D.; Tuttle, Laura; Zhang, Ying Jenny (Journal of Financial and Quantitative Analysis, 2012)
Abstract We find a strong tendency for positive returns during the overnight period followed by reversals during the trading day. This behavior is driven by an opening price that is high relative to intraday prices. It is concentrated among stocks that have recently attracted the attention of retail investors, it is more pronounced for stocks that are difficult to value and costly to arbitrage, and it is greater during periods of high overall retail investor sentiment. The additional implicit transaction costs for retail traders who buy high-attention stocks near the open frequently exceed the effective half spread.